Exploring local variation in the use of out-of-home care in England using linked administrative data - Louise Mc Grath-Lone; Katie Harron; Lorraine Dearden; Bilal Nasim; Ruth Gilbert (International Journal of Population Data Science, 2017)
ABSTRACT